2020
DOI: 10.1038/s41419-020-2508-y
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from human embryonic stem cell-derived cardiovascular progenitor cells promote cardiac infarct healing through reducing cardiomyocyte death and promoting angiogenesis

Abstract: Human pluripotent stem cells (hPSCs)-derived cardiovascular progenitor cells (CVPCs) are a promising source for myocardial repair, while the mechanisms remain largely unknown. Extracellular vesicles (EVs) are known to mediate cell-cell communication, however, the efficacy and mechanisms of hPSC-CVPC-secreted EVs (hCVPC-EVs) in the infarct healing when given at the acute phase of myocardial infarction (MI) are unknown. Here, we report the cardioprotective effects of the EVs secreted from hESC-CVPCs under normox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 72 publications
(121 reference statements)
3
92
2
Order By: Relevance
“…Similar to previous studies that reported that VEGF-A/B could readjust endothelial cells and adipocytes metabolic pathways to favor uptake, transport and oxidation of fatty acids and glucose across and into cells 22,57,58 , besides inducing stem cell differentiation into cardiomyocytes [59][60][61][62] . Our results show that VNS and ACh-induced VEGF-A primarily involved in glucose uptake while induced VEGF-B mainly participated in lipid uptake in myocytes, suggesting that inactivated FoxO3A by VNS triggered the alteration of cardiomyocytes phenotype switch and corresponding metabolic improvement targeting VEGF-A/B.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to previous studies that reported that VEGF-A/B could readjust endothelial cells and adipocytes metabolic pathways to favor uptake, transport and oxidation of fatty acids and glucose across and into cells 22,57,58 , besides inducing stem cell differentiation into cardiomyocytes [59][60][61][62] . Our results show that VNS and ACh-induced VEGF-A primarily involved in glucose uptake while induced VEGF-B mainly participated in lipid uptake in myocytes, suggesting that inactivated FoxO3A by VNS triggered the alteration of cardiomyocytes phenotype switch and corresponding metabolic improvement targeting VEGF-A/B.…”
Section: Discussionsupporting
confidence: 88%
“…The authors showed that RIC and RIC exosomes significantly improved cardiac function and blood vessel formation, and decreased collagen deposition 28 days post-MI. Wu et al ( 2020 ), demonstrated that the intramyocardial injection of EVs from ESC-derived cardiovascular progenitor cells (CVPCs) cultured under normoxia or hypoxia could significantly improve cardiac function, vascularisation and cardiomyocyte survival, and reduce fibrosis at 28 days in a mouse MI model. More importantly, EVs secreted from ESC-CVPC cultured under hypoxia had a better benefit in improving cardiac function post-MI.…”
Section: Evs In Neovascularisationmentioning
confidence: 99%
“…Increasing evidence suggests that the interactions of lncRNAs with miRNAs play a critical role in the regulation of angiogenesis (Zhao et al, 2020 ). Moreover, lncRNAs may be selectively packaged into EVs and transferred between cells, improving cardiac function and vascularisation and reducing fibrosis post-MI (Wu et al, 2020 ). Circular RNAs (circRNAs) have also emerged as novel regulators of EC function and angiogenesis (e.g., CANRIL, CZNF292, Circ_0010729,Circ_0003575, Circ_0054633, Circ_0000109) (Zhang and Huang, 2020 ).…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Additionally, miR-133a-cardiac progenitor cells clearly improved cardiac function in a rat myocardial infarction model by reducing fibrosis and hypertrophy and increasing vascularization and cardiomyocyte proliferation [ 44 ]. The cardiac precursor cell-secreted exosomes promote the infarct healing through the improvement of cardiomyocyte survival and angiogenesis, and the cardioprotective effects can be enhanced by hypoxia conditioning of cardiac precursor cells and are partially contributed by MALAT1 via targeting the miRNA [ 45 ]. In contrast, exosomes from cardiac progenitor cells have also been shown to stimulate cell migration [ 46 ].…”
Section: Exosomes Derived From Different Cell Sourcesmentioning
confidence: 99%